Neutrophil extracellular traps mediate joint hyperalgesia induced by immune inflammation. (26th December 2020) - Schneider, Ayda Henriques; Machado, Caio Cavalcante; Veras, Flávio Protásio; Maganin, Alexandre Gomes de Macedo; de Souza, Flávio Falcão Lima; Barroso, Lívia Corrêa; de Oliveira, Renê Donizeti Ribeiro; Alves-Filho, José Carlos; Cunha, Thiago Mattar; Fukada, Sandra Yasuyo; Louzada-Júnior, Paulo; da Silva, Tarcília Aparecida; et al.
Abstract: Objective: To evaluate the role of neutrophil extracellular traps (NETs) in the genesis of joint hyperalgesia using an experimental model of arthritis and transpose the findings to clinical investigation. Methods: C57BL/6 mice were subjected to antigen-induced arthritis (AIA) and treated with Pulmozyme (PLZ) to degrade NETs or Cl-amidine to inhibit NET production. Oedema formation, the histopathological score and mechanical hyperalgesia were evaluated. NETs were injected intra-articularly in wild type (WT), Tlr4 −/−, Tlr9 −/−, Tnfr1 −/− and Il1r −/− mice, and the levels of cytokines and Cox2 expression were quantified. NETs were also quantified from human neutrophils isolated from RA patients and individual controls. Results: AIA mice had increased NET concentration in joints, accompanied by increased Padi4 gene expression in the joint cells. Treatment of AIA mice with a peptidyl arginine deiminase 4 inhibitor or with PLZ inhibited the joint hyperalgesia. Moreover, the injection of NETs into joints of naïve animals generated a dose-dependent reduction of mechanical threshold, an increase of articular oedema, inflammatory cytokine production and cyclooxygenase-2 expression. In mice deficient for Tnfr1, Il1r, Tlr4 and Tlr9, joint hyperalgesia induced by NETs was prevented. Last, we found that neutrophils from RA patients were more likely to release NETs, and the increase in synovial fluid NET concentration correlated with an increase in joint pain. Conclusion: The findings indicate that NETs cause hyperalgesia possibly through Toll-like receptor (TLR)-4 and TLR-9. These data support the idea that NETs contribute to articular pain, and this pathway can be an alternative target for the treatment of pain in RA.